Phenotypic Characterization and Antibiotics Combination Approach to Control the Methicillin-resistant Staphylococcus aureus (MRSA) Strains Isolated from the Hospital Derived Fomites - Dudhagara, Pravin R; Ghelani, Anjana D; Patel, Rajesh K (Asian Journal of Medical Sciences, 2011)
Objective: The emergence of antibiotic resistant Stphylococcus aureus strains have resulted in significant treatment difficulties which have imposed a burden on health care systems and simultaneously intensifying the need for new antimicrobial agents. Therefore, we have designed the study to determine the prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) and their antimicrobial susceptibility pattern along with evaluation of antibiotic combination approach. Material & Methods: Isolation and identification of MRSA was carried out using Mannitol salt agar followed by Baird-Parker Agar and Vojel-Johnson Agar media. Strains were tested for the sensitivity against five β-lactum, two macrolide and one fluoroquinolone class of antibiotic. Further sensitivity was confirmed using 9 diverse- second and third generation antibiotics. MIC value of individual and mixture of antibiotics were measured using Mueller-Hinton broth. Results: Total 10 stains of S. aureus were isolated and characterised using standard biochemical tests. They were identified using on-line identification tool- GIDEON (Global Infectious Disease and Epidemiology Network). Almost 50% strains were reported having variable reaction against at least one or more antibiotic. By the use of augmentin (30μg), cephotaxime (30μg), ceftriaxone (30μg), cefuroxime (30μg), ciprofloxacin (5μg), clindamycin (2μg), gentamycin (10μg), lincomycin (2μg) and tobramycin (10μg) further susceptibility tesing was carried out which reveals absolute resistant in 70% of strains, whereas, remeaning strains were seen having variable responses against five antibiotics. However, with comparison to standard antibiotic zone of inhibition, all strains were categorized as a resistant. An individual application of ampicillin, tetracycline and amikacin required higher concentration to inhibited all the stains while combination of two or three antibiotics were identified having low MIC value. Combination of tetracycline with sulbactam and cefoperazone was found best to contol MRSA. Conclusion: Study highlights the wide spread presence of MRSA strains in fomites derived from hospital. These indicate the need of more precaution in clinic area to control the spread of the MRSA. Amalgamation of antibiotics is an effective remedy for MRSA infections and promising approach in developing country. Key Words: Antibiotics combination; fomites; MRSA; Staphylococcus aureus DOI: http://dx.doi.org/10.3126/ajms.v2i2.4258 Asian Journal of Medical Sciences 2 (2011) 72-78